Laporan Sementara Mengenai Geologi Daerah Ombilin Pesisir Utara Danau Singkarak - John Katili; Kamal Kamal (Institute for Research and Community Services (LPPM) ITB, 1961)
DETAILED GEOLOGICAL MAPPING WAS CARRIED OUT IN THE OMBILIN AREA, North of Lake Singkarak in order to study more closely the Late Palaeozoic_Early Mesozoic volcanic sedimentary deposits known as the Silungkang formation, the Triassic and the so-called Pre-Permian granite of Guguk Bulat. Some fusulinas of the Silungkang formation were determined and considered to be as Permian age*.The Silungkang formation is correlated with similar sedimentary volcanic series of Gk. Gie Sie Top Top and the Lake Air Tawar of North Sumatra. Field investigations have revealed that a part of the limestone in the upper stream of the river Lurah Tambang does not belong to the Triassic, but to the Silungkang formation. Furthermore it became evident that the Pre-Premian granite does not exist, on the contrary we have to consider the arkosic rock of Guguk Bulat as a part of the Tertiary quartzstandstone formation, resulting from weathering of a younger granite, possibly Cretaceousin age. The quartzdiorite which occurs as small bodies between the granite and the Pre-Tertiary volcanic products, is considered as altered andesitic rocks of the Silungkang volcanic series, caused by the formation of granites.*) The determination was done by MARKS, former lecturer in palaeontology, of the faculty of Science, University of Indonesia, Bandung